The Materiality of the Afro-Brazilian counter-narrative: from the lugar de fala to the ethnographic case of the MUNCAB museum in Salvador de Bahia (Altre Modernità, 2024)
This article offers a reflection on the empowerment strategies of contemporary Afro-Brazilian communities in Salvador de Bahia city. The colloquial expression lugar de fala (‘place of speech’) is currently used in the local context to express the idea of black communities’ self-determination as a process of creation of new representations which capture the complexity of the Afro-descending identity. Racist discourses are produced and reproduced both on the linguistic-semantic and on the material level of aesthetic-visual representation in the Bahian context. Some results of the field research conducted in 2019 in the federal state of Bahia will be presented after a brief historical survey on the role of racial categorization of Brazilian citizens in the construction of the nation-state. The political contestation of the negras (‘black’) communities will be presented through the ethnographic case of the Museu Nacional da Cultura Afro-brasileira (called MUNCAB). This will allow us to reflect on the centrality of sensory experience for the construction of national counter-narrative history and to take into question the modernist epistemological assumption of ‘time’.
Keywords: Postcolonial studies; blackness; racism; counter-narrative; time; aesthetic